Untagging on social media: Who untags, what do they untag, and why?. (April 2017) - Birnholtz, Jeremy; Burke, Moira; Steele, Annie
Abstract: Social network profiles display individuals' posts and content left by their friends, such as wall posts and photo tags. Sometimes content posted and tagged by others is inconsistent with a person's desired self-image. One strategy that people use to increase the distance between their identity and content they don't like is to untag themselves. Tagging and untagging pose important questions for traditional theories of self-presentation, which describe the projection of one's own desired identity and others' response to that projection. Tagging reverses this role by allowing others to project a person's identity, and forcing that person to respond. Using de-identified, aggregated behavioral data from Facebook and a survey of 802 people, this paper aims to explore this shift by asking whether untagging occurs similarly to other self-presentation behavior and how people view this strategy. Results suggest that untagging differs from traditional self-presentation tactics in three key respects: it is used more by more experienced users, it occurs when there are gender and age differences between tagger and target, and it is seen as an easy way to mitigate the negative effects of annoying or embarrassing content. Highlights: Experienced users Untag more; technical skill and site familiarity may play a role. More untagging when there are gender/age differences that impact audience assumptions. Untagging seen as an easy way to mitigate annoying or embarrassing content.